Japan's new politics and the U.S.-Japan alliance - Smith, Sheila A. (Council on Foreign Relations, 2014)
Japan's new politics challenge some basic assumptions about U.S.-Japan alliance management. From the election of the Democratic Party of Japan (DPJ) in 2009 to the return of the Liberal Democratic Party (LDP) in 2012, this new era of alternating parties in power has revealed the growing importance of Japan's domestic politics in shaping alliance cooperation. The fluidity in electoral outcomes in recent parliamentary elections reveals the extent of Japanese voter frustration with the government. A divided Diet challenged the Japanese government's ability to implement policy. Policy reform is in high demand in Tokyo, and the U.S.-Japan alliance is not immune to the popular call for greater accountability as past choices are increasingly subjected to policy review.